Event-triggered reliable dissipative filtering for the delay nonlinear system under networked systems with the sensor fault. Issue 3 (3rd March 2020) - Aslam, Muhammad Shamrooz; Chen, Ziran
ABSTRACT: This paper investigates the problem of fuzzy filter design for a class of delayed nonlinear system under random sensor faults with an event-triggered (ET) mechanism. (1) To estimate the dynamics of nonlinear plant, a T–S fuzzy model is manipulated. Random variables are disclosed to express the sensor fault. (2) To take some advantages over existing one, a variable ET mechanism is offered in networked systems (NSs). Under the ET mechanism, sensor data are released only when the plant's measurement (sampled) violate specific threshold of the event condition. (3) Another purpose of this article is to design filters involving system state delays. Then, by using a novel fuzzy Lyapunov–Krasovskii function approach with free weighting matrix technique, dissipative filter design of ET delay networked control systems is proposed. We consider both the sensor fault and ET scheme simultaneously. The simulation example is given to demonstrate the effectiveness of design method.